2017
DOI: 10.3171/2017.3.focus1710
|View full text |Cite
|
Sign up to set email alerts
|

Robotic versus fluoroscopy-guided pedicle screw insertion for metastatic spinal disease: a matched-cohort comparison

Abstract: OBJECTIVERobot-guided pedicle screw placement is an established technique for the placement of pedicle screws. However, most studies have focused on degenerative disease. In this paper, the authors focus on metastatic spinal disease, which is associated with osteolysis. The associated lack of dense bone may potentially affect the automatic recognition accuracy of radiography-based surgical assistance systems. The aim of the present study is to compare the accuracy of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
84
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 125 publications
(88 citation statements)
references
References 25 publications
4
84
0
Order By: Relevance
“…20 Breaches were also quantified (Grades A-E) in accordance with the literature. 4,6,18,19,[21][22][23][24][25][26][27] Screw malposition as described by Kim et al 11 found deviations of 0 to 2 mm to be clinically insignificant; 2 to 4 mm, probably safe; and greater than 4 mm, questionably safe. In the present study, conventional MIS and open techniques resulted in an overall breach rate (>2 mm) of 20% and 32.5%, respectively, within the ranges reported by Gelalis et al 15 ; 19 of 20 breaches occurred laterally, a trend in agreement with reported literature.…”
Section: Discussionmentioning
confidence: 99%
“…20 Breaches were also quantified (Grades A-E) in accordance with the literature. 4,6,18,19,[21][22][23][24][25][26][27] Screw malposition as described by Kim et al 11 found deviations of 0 to 2 mm to be clinically insignificant; 2 to 4 mm, probably safe; and greater than 4 mm, questionably safe. In the present study, conventional MIS and open techniques resulted in an overall breach rate (>2 mm) of 20% and 32.5%, respectively, within the ranges reported by Gelalis et al 15 ; 19 of 20 breaches occurred laterally, a trend in agreement with reported literature.…”
Section: Discussionmentioning
confidence: 99%
“…In the existing studies, a relatively high proportion indicated that the accuracy of screw placement in the robot group has been improved substantially or significantly. The accuracy of robot‐assisted surgery proposed by Solomiichuk et al was only 84.4% . Meanwhile, Lonjon et al found that Rosa robot‐assisted screw placement was accurate 97.3% of the time, compared with 92% for the freehand group .…”
Section: Discussionmentioning
confidence: 99%
“…Kim et al compared a prospective randomized controlled trial of 78 patients conventional fluoroscopy‐guided against robot‐assisted PS implantation and showed that robotic‐assisted PS placement was associated with fewer proximal facet joint violations and better convergence orientation; the 1‐year follow‐up showed no clinical difference . Solomiichuk et al compared in 70 patients the SpineAssist with fluoroscopy‐guided PS implantation in spinal metastasis and showed equipoise in accuracy, radiation time, and postoperative infection rates. Similar findings were published by Molliquaj et al in 71 patients.…”
Section: Discussionmentioning
confidence: 99%
“…We demonstrated that combining the ROSA One Spine system and showed that robotic-assisted PS placement was associated with fewer proximal facet joint violations and better convergence orientation; the 1-year follow-up showed no clinical difference. 23 Solomiichuk et al 24 Lefranc et al reported very satisfying results concerning accuracy and the rate of complications and concluded that PS positioning did not require years of experience and the learning curve was steep. 19 The main advantage of using a…”
Section: Discussionmentioning
confidence: 99%